Optimalisasi Kualitas Laba: Kasus Pada Perusahaan Sektor Consumer Non-Cyclicals Di Indonesia - Dinda Fitri Novia Lestari; Shinta Permata Sari (MEASUREMENT : Jurnal Program Studi Akuntansi, 2025)
This study examines the influence of four determinant variables on earnings quality in companies within the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. Employing a quantitative approach utilizing secondary data from the annual reports of 73 sampled companies that selected using purposive sampling methods. Hypothesis testing through multiple linear. The study findings prove that, among the four determinants examined, only liquidity and capital structure influence the earnings quality. Meanwhile, profit potential and Investment Opportunity Set do not influence the earnings quality. These results indicate that, in the context of consumer non-cyclicals sector, liquidity and capital structure have a more prominent role in shaping earnings quality compared to profit potential and Investment Opportunity Set.